2004
DOI: 10.1083/jcb.200307137
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for ADAM10 and ADAM17 in ectodomain shedding of six EGFR ligands

Abstract: All ligands of the epidermal growth factor receptor (EGFR), which has important roles in development and disease, are released from the membrane by proteases. In several instances, ectodomain release is critical for activation of EGFR ligands, highlighting the importance of identifying EGFR ligand sheddases. Here, we uncovered the sheddases for six EGFR ligands using mouse embryonic cells lacking candidate-releasing enzymes (a disintegrin and metalloprotease [ADAM] 9, 10, 12, 15, 17, and 19). ADAM10 emerged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
981
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 901 publications
(1,034 citation statements)
references
References 62 publications
46
981
1
6
Order By: Relevance
“…Our analyses of an uncleavable human FasL mutant (Supplementary Figure 1) showed that the release of sFasL was completely abrogated in human and murine cells, indicating that despite the loose cleavage specificity the protease susceptible region is located within this region. ADAM10 has been implicated before in the shedding of different substrates including CD44, 37 amphiregulin, 38 N-cadherin, 21 E-cadherin 24 and the neuronal adhesion molecule L1. 39 For some of these substrates, ADAM10 is responsible for both the constitutive and the inducible shedding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses of an uncleavable human FasL mutant (Supplementary Figure 1) showed that the release of sFasL was completely abrogated in human and murine cells, indicating that despite the loose cleavage specificity the protease susceptible region is located within this region. ADAM10 has been implicated before in the shedding of different substrates including CD44, 37 amphiregulin, 38 N-cadherin, 21 E-cadherin 24 and the neuronal adhesion molecule L1. 39 For some of these substrates, ADAM10 is responsible for both the constitutive and the inducible shedding.…”
Section: Discussionmentioning
confidence: 99%
“…293T cells, MEFs from ADAM9 À/À , ADAM10 À/À , ADAM15 À/À , ADAM17 À/À mice and respective wild-type animals were generated and characterized as described elsewhere. 20,38 All cells were grown in Dulbecco's modified Eagle's medium with high glucose (PAA Laboratories, Pasching, Austria), supplemented with antibiotics and 10% fetal calf serum (FCS). Cells were transfected with FuGENE 6 (Roche Applied Science, Mannheim, Germany) according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…• Epidermal-growth-factor receptor (EGFR) ligands need to be processed to function 28,[142][143][144] Cell survival…”
Section: Proliferationmentioning
confidence: 99%
“…Expression of these two proteins in precursor cell cultures, and their persistence in differentiating conditions, suggested that one of these enzymes, or both, participate in determining the cell fate of neural precursors. A systematic characterization of EGFR ligand processing by ADAM-10 and ADAM-17 [40,47] demonstrated that ADAM-10 is the major convertase of EGF and betacellulin, whereas ADAM-17 is the main sheddase of TGF-a, HB-EGF, epiregulin, amphiregulin, and epigen. Interestingly, among the four EGFR ligands studied in this work, specifically those that were substrates for ADAM-17 (TGF-a, HB-EGF, and amphiregulin) were expressed in the cultured cells, whereas EGF mRNA was undetectable.…”
Section: Adam-17 and Tgf-a Are Directly Involved In Npc Differentiationmentioning
confidence: 99%